Effects of physical training on body weight, pulmonary function and dietary patterns in adolescents with obesity - Francesco Tafuri; Francesca Latino; Hendra Setyawan; Khoiril Anam; Nugroho Susanto; Domenico Tafuri; Filomena Mazzeo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Physical activity offers a powerful tool to address the challenges faced by obese teenagers. By promoting social inclusion, improving physical health, and boosting mental well-being, sports can significantly enhance their overall quality of life. Our research discusses the negative effects of obesity in adolescents and the benefits of a sports program when addressing these issues. The study involved 60 participants (30 males and 30 females) aged 14-16 for a period of eight months. Results showed significant weight loss for most participants: 26 participants lost around 10% of their body weight, another group lost around 8%, and only 4 subjects did not experience significant weight change. The study also observed a 9.5% improvement in motor skills on average. The mean weight loss difference between intervention and control was 9.30%. The study emphasizes the detrimental effects of obesity in adolescents and highlights the effectiveness of physical activity programs in promoting weight loss, enhancing respiratory function and induce healthy eating habits among obese adolescents. It also underscores the positive social and lifestyle benefits associated with regular physical activity.